Over a million students use our free study notes to help them with their homework
The way to go about a question like this is to break it down into steps; rather than trying to multiply all the brackets at once expand two first then multiply by the third. ------------------------------...
Group the like terms together to make the equation less messy leaving the equation equal to 0.Simplify the long quadratic equation into brackets.Each bracket must be equal to 0 to fulfil the equation.When...
steps as follows:x times x = x22 times 5 = 102 times x = 2xx times 5 = 5xthen add these together:y = x2 + 7x +10x = -2, -5; y = 0, 10
Use implicit differentiation on original equation- 12x + 3x(dy/dx) + 3y - 2y(dy/dx) = 0 dy/dx= -12x -3y/(3x-2y) at A, x= -5 and y= 10 therefore, dy/dx=-6/7 To find the normal of t...
This requires the chain rule and the product rule to be used to differentiate the function. The substitution u = x2 can be used to make this easier. Using this, du/dx = 2x and y = (u-5)eu<...
←
515
516
517
518
519
→
Internet Safety
Payment Security
Cyber
Essentials